Africa is my home : a child of the Amistad - Edinger, Monica, 1952- (Candlewick Press, 2015)
Tells the story of nine-year-old Margru who is sold by her father for a bag of rice, captured by slave traders, and sent to America aboard the Amistad. After the mutiny aboard the ship, she is arrested and defended in court by John Quincy Adams. Eventually Margru is educated and returns to Africa as a teacher.